Aqueous-phase oxidation of three phenolic compounds by hydroxyl radical: Insight into secondary organic aerosol formation yields, mechanisms, products and optical properties. (15th February 2020) - Ye, Zhaolian; Zhuang, Yu; Chen, Yantong; Zhao, Zhuzi; Ma, Shuaishuai; Huang, Hongying; Chen, Yanfang; Ge, Xinlei
Abstract: This work performed a systematic investigation on the aqueous hydroxyl radical (OH) - induced photochemical oxidation of three modestly-soluble precursors from biomass combustion including 4-methylsyringol (DMP), eugenol (Eug), and 2, 4, 6-trimethylphenol (TRMP) under both simulated sunlight and ultraviolet (UV) light irradiations. An Aerodyne soot particle aerosol mass spectrometer (SP-AMS) was used to monitor the bulk chemical and elemental compositions of aqueous secondary organic aerosol (aqSOA) formed. AqSOA mass yields varied in ranges of 80–190% and 0–200% under sunlight and UV light conditions, respectively. AqSOA oxygen-to-carbon (O/C) ratio and carbon oxidation state increased steadily under sunlight + OH condition, but increased then decreased under UV + OH condition. Organic acids including malic acid, glycolic acid, formic acid and oxalic acid were formed, and their total accounted for 12% of SOA mass. The UV–vis spectral change suggested formation of light-absorbing organics. Reaction pathways were proposed by combining gas chromatography-mass spectrometry (GC-MS) and SP-AMS results. Under sunlight + OH condition, oligomerization, functionalization, and fragmentation processes all involved in aqSOA evolution, with more contribution from functionalization via hydroxylation and oxygenation reactions. Reaction mechanism of UV + OH oxidation was initially dominated by functionalization then by fragmentation, indicating by the decrease of total organic carbon (TOC) contents, formation of small organic acids and low-molecular-weight products. Our work highlights that combination of SP-AMS with GC-MS is a powerful method for laboratory investigation of aqueous-phase reactions. Highlights: This work investigated aqueous OH oxidation of three phenolic species. Aerodyne SP-AMS was used to monitor the changes of aqSOA compositions. Large aqSOA yields were found and production of organic acids was significant. Light-absorbing organic species were produced during aqueous processing.